Microorganisms in coastal wetland sediments: a review on microbial community structure, functional gene, and environmental potential - Liang, Shen; Li, Huai; Wu, Haitao; Yan, Baixing; Song, Aiwen (Frontiers in Microbiology, 2023)
Coastal wetlands (CW) are the junction of the terrestrial and marine ecosystems and have special ecological compositions and functions, which are important for maintaining biogeochemical cycles. Microorganisms inhabiting in sediments play key roles in the material cycle of CW. Due to the variable environment of CW and the fact that most CW are affected by human activities and climate change, CW are severely degraded. In-depth understanding of the community structure, function, and environmental potential of microorganisms in CW sediments is essential for wetland restoration and function enhancement. Therefore, this paper summarizes microbial community structure and its influencing factors, discusses the change patterns of microbial functional genes, reveals the potential environmental functions of microorganisms, and further propose future prospects about CW studies. These results provide some important references for promoting the application of microorganisms in material cycling and pollution remediation of CW.